Ergonomics in machine tool design: second progress report on M.T.I.R.A. research project - Easterby, R. S. (College of Aeronautics, 1963)
This report is the second of a series of reports, to be issued every six months, describing the progress of a research project on ergonomics in relation to machine tool design. The report covers, in broad outline, the progress made, and some projects anticipated in the ensuing year. Separate detailed technical reports will be issued from time to time, as experimental and survey data become available. The progress reports are numbered in The College of Aeronautics Notes series. The first report, issued in October, 1962, is CoA Note 150, Part 1. The technical reports will also be numbered in the series.